3-3.7b=10.3b+10

Subtract 10.3b from both sides of the equation.

3-3.7b-10.3b=10

Subtract 10.3b from -3.7b.

3-14b=10

3-14b=10

Subtract 3 from both sides of the equation.

-14b=10-3

Subtract 3 from 10.

-14b=7

-14b=7

Divide each term in -14b=7 by -14.

-14b-14=7-14

Cancel the common factor of -14.

b=7-14

Simplify 7-14.

Cancel the common factor of 7 and -14.

Factor 7 out of 7.

b=7(1)-14

Cancel the common factors.

Factor 7 out of -14.

b=7⋅17⋅-2

Cancel the common factor.

b=7⋅17⋅-2

Rewrite the expression.

b=1-2

b=1-2

b=1-2

Simplify the expression.

Move the negative in front of the fraction.

b=-12

Divide 1 by 2.

b=-1⋅0.5

Multiply -1 by 0.5.

b=-0.5

b=-0.5

b=-0.5

b=-0.5

Solve for b 3-3.7b=10.3b+10